Professional Evolution of School Teacher on Basis of Advanced Pedagogical Experience - N. L. Sokolova (Научный диалог)
The review of the monographic study by M. S. Britkevich and M. G. Sergeeva “Andragogical support of innovative activity of teachers in the system of professional development” states that this scientific work should be evaluated taking into account the state order for the formation and development of innovative educational infrastructure and building a new strategy of effective activity in the field of secondary, higher and additional education. The need of a modern school for teachers who are able to integrate pedagogical innovations into professional practice (both individual and mass) indicates the need to create conditions for more effective support of innovative activity of teachers in the framework of professional development, as well as for their perception of certain rules of innovative behaviour and the creation of new varieties, algorithms and methods of systematization and popularization of advanced teaching experience. The study of the problems associated with the introduction of the relevant innovations in the educational process determines the main indicators and evaluation criteria of the reviewed work.